2014
DOI: 10.1152/ajprenal.00520.2013
|View full text |Cite
|
Sign up to set email alerts
|

SGLT2 inhibitor empagliflozin reduces renal growth and albuminuria in proportion to hyperglycemia and prevents glomerular hyperfiltration in diabetic Akita mice

Abstract: Our previous work has shown that gene knockout of the sodium-glucose cotransporter SGLT2 modestly lowered blood glucose in streptozotocin-diabetic mice (BG; from 470 to 300 mg/dl) and prevented glomerular hyperfiltration but did not attenuate albuminuria or renal growth and inflammation. Here we determined effects of the SGLT2 inhibitor empagliflozin (300 mg/kg of diet for 15 wk; corresponding to 60-80 mg·kg(-1)·day(-1)) in type 1 diabetic Akita mice that, opposite to streptozotocin-diabetes, upregulate renal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

41
423
2
22

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 436 publications
(488 citation statements)
references
References 44 publications
(94 reference statements)
41
423
2
22
Order By: Relevance
“…In vitro and in vivo work has suggested that sodium glucose cotransport inhibition reduces markers of inflammation and fibrosis [18,19,[29][30][31]. Although we did not measure inflammatory markers in the present trials, future studies should assess the effect of SGLT2 inhibition on pro-inflammatory and pro-fibrotic mechanisms in diabetes and associated kidney disease.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In vitro and in vivo work has suggested that sodium glucose cotransport inhibition reduces markers of inflammation and fibrosis [18,19,[29][30][31]. Although we did not measure inflammatory markers in the present trials, future studies should assess the effect of SGLT2 inhibition on pro-inflammatory and pro-fibrotic mechanisms in diabetes and associated kidney disease.…”
Section: Discussionmentioning
confidence: 85%
“…Previous experimental work using different animal models of kidney disease have demonstrated that SGLT2 inhibition alleviates renal damage. In Akita and streptozotocin-induced animal models of insulin-deficient diabetes, SGLT2 inhibition reduced albuminuria [18][19][20]. SGLT2 inhibition has similar anti-albuminuric effects in animal models of type 2 diabetes [21], including recent evidence that empagliflozin reduced albuminuria, independent of effects on BP or hyperglycaemia, in BTBR ob/ob mouse models of type 2 diabetes [22].…”
Section: Discussionmentioning
confidence: 93%
“…Simultaneous SGLT2-RAAS blockade induces afferent arteriole constriction (SGLT2 inhibition) and efferent arteriole vasodilatation (RAAS blockade), thereby more thoroughly counteracting early intrarenal hemodynamic abnormalities underlying glomerular hyperfiltration in CKD. Additionally, SGLT2 inhibitors have decreased inflammatory and fibrogenic responses, oxidative stress, and cell apoptosis in diverse experimental models of CKD (128).…”
Section: Targeting the Renal Tubule To Improve Ckd And Nafldmentioning
confidence: 99%
“…당뇨병에서 SGLT2 억제제 투여에 의해서 이러한 과여 과를 줄일 수 있다는 실험연구와 임상 연구 결과들은 많 이 보고되었다 [4,8,10]. 즉, SGLT2 억제제가 근위세뇨관 에서 과흡수를 억제하면 원위세뇨관으로 나트륨 전달이 증가하고 염분의 증가가 macula densa에서 감지되면 afferent arteriole을 수축시키는 tubuloglomerular feedback이 작동하여 사구체의 과여과가 개선되어 사구 체여과율이 감소하며 당뇨병 환자에서 empagliflozin 투여에 의한 과여과의 감소 정도는 레닌-안지오텐신-알도스테론 축(renin-anigotensin-aldosterone system, 이하 RAAS)의 억제 효과와 비슷할 정도라고 보고되었다( Fig.…”
Section: 근위세뇨관에서의 과흡수 (Hyperreabsorption)와 Tubuloglomerular Feedback의unclassified
“…그 외에 세포 수준의 실험 조건하에서나 당뇨병성 실험 동물 모델에서 신장 근위관세포가 고혈당에 노출되면 염증반응이나 섬유화를 증가시키는 기전이 활성화되는 데, SGLT2 억제제는 이 기전의 활성을 억제하는 효과 가 있다 (Fig. 1) [7,8].…”
unclassified